Conformity and conflict readings in cultural anthropology - Spradley, James P.; McCurdy, David W. (Upper Saddle River, New Jersey Pearson Education, Inc., 2012)
This volume is an anthology of articles that cover a broad range of theoretical perspectives and demonstrate basic anthropological concepts. It incorporates successful articles from past editions and fresh ideas from the field to show fascinating perspectives on the human experience. The authors have added additional selections on globalization, medical anthropology, and applied anthropology.
[Pt.] 1. Culture and ethnography. Ethnography and culture / James P. Spradley -- Eating Christmas in the Kalahari / Richard Borshay Lee -- Fieldwork on prostitution in the era of AIDS / Claire E. Sterk -- Nice girls don't talk to Rastas / George Gmelch -- [Pt.] 2. Language and communication. Shakespeare in the bush / Laura Bohannan -- Whorf revisited : you are what you speak / Guy Deutscher -- Manipulating meaning : the military name game / Sarah Boxer -- Conversation style : talking on the job / Deborah Tannen -- [Pt.] 3. Ecology and subsistence. The hunters : scarce resources in the Kalahari / Richard Borshay Lee -- Eskimo science / Richard Nelson -- Domestication and the evolution of disease / Jared Diamond -- Forest development the Indian way / Richard K. Reed -- [Pt.] 4. Economic systems. Reciprocity and the power of giving / Lee Cronk -- Poverty at work : office employment and the crack alternative / Philippe Bourgois -- Cocaine and the economic deterioration of Bolivia / Jack Weatherford -- Malawi versus the World Bank / Sonia Patten -- [Pt.] 5. Kinship and family. Mother's love : death without weeping / Nancy Scheper-Hughes -- Family and kinship in village India / David W. McCurdy -- Polyandry : when brothers take a wife / Melvyn C. Goldstein -- Uterine families and the women's community / Margery Wolf -- [Pt.] 6. Identity, roles, and groups. You@work : jobs, identity, and the Internet / Brenda Mann -- The opt-out phenomenon : women, work, and identity in America / Dianna Shandy and Karine Moe -- Do Muslim women really need saving? / Lila Abu-Lughod -- Mixed blood / Jefferson M. Fish -- [Pt.] 7. Law and politics. Cross-cultural law : the case of the gypsy offender / Anne Sutherland -- Life without chiefs / Marvin Harris -- The founding Indian fathers / Jack Weatherford -- [Pt.] 8. Religion, magic, and world view. Taraka's ghost / Stanley A. Freed and Ruth S. Freed -- Baseball magic / George Gmelch -- Run for the wall : an American pilgrimage / Jill Dubisch -- Body ritual among the Nacirema / Horace Miner -- [Pt.] 9. Globalization. How sushi went global / Theodore C. Bestor -- Village walks : tourism and globalization among the Tharu of Nepal / Arjun Guneratne and Kate Bjork -- The road to refugee resettlement / Dianna Shandy -- Global women in the new economy / Barbara Ehrenreich and Arlie Russe Hochschild -- [Pt.] 10. Culture change and applied anthropology. Advice for developers : Peace Corps problems in Botswana / Hoyt S. Alverson -- Medical anthropology : leprosy on the Ganges / Ron Barrett -- Public interest ethnography : women's prisons and health care in California / Rachael Stryker -- Using anthropology / David W. McCurdy -- Career advice for anthropology undergraduates / John T. Omohundro.
Includes index.
Keywords: Ethnology; Anthropology